Implementasi Digital Marketing pada UMKM di Kecamatan Lembang terhadap Tingkat Penjualan pada Masa Pandemi Covid-19 - Handita Gumilar; Kania Nurcholisah; Irena Paramita Pramono (Bandung Conference Series: Accountancy, 2023)
Abstract. The development of information technology has been so rapid, especially since the Covid-19 pandemic, all forms of community activities have been shifted online to avoid direct interaction. At this time, MSMEs need to start a digital marketing strategy that can reach a wider selling market. Identification of problems in this study include: (1) How is the Implementation of Digital Marketing for MSMEs in Lembang District; (2) What is the sales level of MSMEs in Lembang District after implementing digital marketing; and (3) How much does digital marketing affect the level of sales to MSMEs in Lembang District. The research population is 207 UMKM in Lembang District. Sampling used the slovin sample test formula so that the sample totaled 36 SMEs. The research method used is a quantitative research method. Instrument testing uses a simple linear regression test with validity and reliability tests. Hypothesis testing uses the MSI method and the classic assumption test uses the Spearman rank. The conclusions of the research include: (1) as many as 83% of MSMEs in Lembang District have implemented digital marketing; (2) there was an increase in sales to SMEs on indicators including: 87% of SMEs experienced an increase in selling prices, 86% of SMEs experienced an increase in demand, 86% of SMEs experienced an increase in competition, and 73% of SMEs experienced an increase in cost efficiency; (3) the implementation of digital marketing has quite an effect on the sales level of MSMEs based on a correlation coefficient of 0.400. Abstrak. Perkembangan teknologi informasi begitu pesat terutama sejak terjadinya pandemi covid-19 segala bentuk aktivitas masyarakat dialihkan secara online untuk menghindari interaksi secara langsung. Pada masa ini, UMKM perlu memulai strategi pemasaran digital yang dapat menjangkau pasar jual lebih luas lagi. Identifikasi masalah pada penelitian ini diantaranya : (1) Bagaimana Implementasi Digital Marketing pada UMKM di Kecamatan Lembang; (2) Bagaimana tingkat penjualan UMKM di Kecamatan Lembang setelah mengimplementasikan digital marketing; dan (3) Seberapa besar digital marketing berpengaruh terharap tingkat penjualan pada UMKM di Kecamatan Lembang. Populasi penelitian merupakan UMKM di Kecamatan lembang sebanyak 207 UMKM. Pengambilan sampel menggunakan rumus uji sampel slovin sehingga sampel berjumlah 36 UMKM. Metode penelitian yang digunakan berupa metode penelitian kuantitatif. Pengujian instrumen menggunakan uji regresi linier sederhana dengan uji validitas dan uji realibilitas. Pengujian hipotesis menggunakan metode MSI dan uji asumsi klasik menggunakan rank spearman. Simpulan penelitian diantaranya : (1) sebanyak 83% UMKM di Kecamatan Lembang telah mengimplementasikan digital marketing; (2) terdapat peningkatan penjualan pada UMKM terhadap indikator diantaranya : 87% UMKM mengalami peningkatan harga jual, 86% UMKM mengalami peningkatan permintaan, 86% UMKM mengalami peningkatan persaingan, dan 73% UMKM mengalami peningkatan efisiensi biaya; (3) implementasi digital marketing cukup berpengaruh terhadap tingkat penjualan UMKM berdasarkan nilai koefisien korelasi sebesar 0.400.